Effects of Astaxanthin on Inflammation and Insulin Resistance in a Mouse Model of Gestational Diabetes Mellitus. Issue 2 (19th May 2020) - Feng, Weihong; Wang, Yanxia; Guo, Na; Huang, Pu; Mi, Yang
Gestational diabetes mellitus (GDM) is a condition in which a hormone made by the placenta prevents the body from using insulin effectively. It is important to find an effective treatment. A mouse model of GDM was used to testify the effects of astaxanthin on glucose tolerance and insulin sensitivity. Production of inflammatory cytokines, reactive oxygen species (ROS), and glucose transporter type 4 (GLUT4) translocation and insulin-related signaling were measured in the presence of astaxanthin both in vivo and in vitro. It was found that astaxanthin improved insulin sensitivity, glucose tolerance, and litter size of offspring and reduced birth weight of offspring and inflammation in GDM mouse. Moreover, astaxanthin increased GLUT4 translocating to membrane without altering its secretion/expression and glucose uptake and consumption in C2C12 skeletal muscle cells. Furthermore, ROS generation and insulin-related signaling inhibited by tumor necrosis factor α was restored by astaxanthin. It is concluded that astaxanthin has the potential to attenuate GDM symptoms by regulating inflammation and insulin resistance in skeletal muscle of pregnant mice. Our findings suggest that astaxanthin could be a promising and effective molecule to treat GDM.